2019
DOI: 10.1177/1059840519850619
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Study of Myopia in Taiwanese School Children: Family, Activity, and School-Related Factors

Abstract: The purpose of the study was to explore how fixed and modifiable family, activity, and school factors affect a student’s myopia risk and severity. We used national cross-sectional data from Taiwanese children in Grades 4–6. Bivariate and multivariate analyses, including logistic and ordinary least squares regression, examined factors related to children’s myopia status and severity. Age, parent myopia, and school district were associated with risk of myopia. One hour or more per day of near work (OR = 1.26) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 54 publications
1
19
0
2
Order By: Relevance
“…The characteristics of all included studies are shown in table 1 and in the appendix (pp 28-29). Ten (30%) studies 18,20,23,27,28,32,[35][36][37][38] met the criteria for inclusion in category one, ten (30%) studies 19,21,22,29,30,[39][40][41][42][43] for inclusion in category two (table 1), and 13 (39%) studies [44][45][46][47][48][49][50][51][52][53][54][55][56] for inclusion in category three (appendix pp [28][29]. Seven (70%) category one studies 18,20,23,27,28,32,35 and four (40%) category two studies 19,22,29,30 were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of all included studies are shown in table 1 and in the appendix (pp 28-29). Ten (30%) studies 18,20,23,27,28,32,[35][36][37][38] met the criteria for inclusion in category one, ten (30%) studies 19,21,22,29,30,[39][40][41][42][43] for inclusion in category two (table 1), and 13 (39%) studies [44][45][46][47][48][49][50][51][52][53][54][55][56] for inclusion in category three (appendix pp [28][29]. Seven (70%) category one studies 18,20,23,27,28,32,35 and four (40%) category two studies 19,22,29,30 were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Seven (70%) category one studies 18,20,23,27,28,32,35 and four (40%) category two studies 19,22,29,30 were included in the meta-analysis. Risk of bias assessment with the JBI Critical Appraisal Checklists revealed the following sources of bias: the absence of valid or reliable measurement of exposure in all 33 studies; the absence of objective standard criteria for measurement of the condition in seven (21%) studies; 22,28,32,[36][37][38]42 no assessment of confounders in nine (27%) studies; 21,39,41,42,45,48,52,55,56 insufficient strategies for dealing with confounders in nine (27%) studies; 21,28,39,40,42,45,48,52,55 incomplete follow-up in three (9%) studies; 19,51,54 the absence of strategies to address incomplete follow-up in four (12%) studies; 19,35,51,54 and unclear reporting of whether participants were free from myopia at baseline in two (6%) studies. 32,…”
Section: Resultsmentioning
confidence: 99%
“…This rapid increase in the prevalence of myopia among the young generation may lead to myopia becoming one of the main blinding causes in the future because high myopia is associated with myopic maculopathy [4] and an increase in glaucomatous optic neuropathy prevalence [5]. Although the causes of myopia remain unclear, numerous studies have suggested its development is caused by environmental and genetic factors [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Children aged 7-9 who read two or more books a week run a three times higher risk of myopia as compared to those children who read two or fewer books a week [21,22]. Children aged 12-13 who hold a book at a distance equal to 29 cm or less when reading run 2.5 times higher risk of myopia; uninterrupted reading that lasts for longer than 30 minutes results in 1.5 times higher risks of myopia [21]; 6-year old children who work at a short distance from objects for more than 1 hour a day run 1.26 times higher risk of myopia [23]. However, if we take into account other significant factors (such as belonging to a specific ethnic group, for example), we should specify that intensity is a leading factor and not a period of time spent working at a short distance from objects.…”
mentioning
confidence: 99%